(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Most important resource of an organization is Human beings. “The wonder of wonder is man, who has infinite capacity tothink, to develop, to invent, to feel, to love, to give, to kill, to respect and to hate, analyze or destroy.”. Human resource Management (HRM) is an provides the possibility of performance change and improvement towards individuals and groups through Management of their knowledge, skills and abilities (KSA’s) necessary for the successful performance of the organization. Our HRD area covers training and Management, organizational Management, career Management and HR practices. An organization’s most valued assets are the people working there who individually and collectively contribute to the achievement of the objectives of the business. The terms human resource management and human resources (HR) have largely replaced the term personnel management as a description of the processes involved in managing people in organizations. Education is an important element of the national Management of any country higher education is of the vital importance for that Management. The innumerable challenges confronting the Indian higher education are several and complex. But some have changed and developed with time, others are newly created by the strengthening of attention and blossoming of opportunities. This paper will highlight the challenges human resource faces in the field of education and on how an organization meets the challenges.